Implementasi Firebase Pada Pengembangan Backend Aplikasi E-Commerce Sihalal Berbasis Mobile - Harry, Soepandi; Andrianto, Anang; Binashrillah, Muhammad Farhan (Faculty of Computer Science, University of Jember, 2024)
A Indonesia has the largest Muslim majority population in the world, with a total of 237.53 million people as of December 31 2021, which means 86.9% of Indonesia's population is Muslim. The law requires businesses to register their products, such as food and drinks. Many applicants received by BPJPH were canceled because the raw materials used did not have halal certificates yet. Products that wish to have halal certificates are produced by MSE entrepreneurs who live in rural areas far from the city center based on the results of field surveys by the Halal Product Process Assistant (P3H). BPJPH seeks to solve theproblem by creating a digital e-commerce platform where users can buy and sell products, especially halal food and beverage raw materials, online. This research aims to produce a backend for SiHALAL using Firebase which is suitable for SiHALAL because it needs to handle large amounts of user, product andorder data and data must be updated in real time. This research uses Black Box Testing as application testing methods. Black Box testing results show that the application can carry out its functionality